The open cluster Tr 14 - Feinstein, Alejandro (1983)
New photoelectric UBVRI data for stars in the young open cluster Tr 14 in the Great Carina Nebula (NGC 3372) are presented. The two-color diagram separates clearly the member from the nonmember stars. Thus, the membership of about 39 stars is suggested. Those located in the compact core of the cluster, have smaller reddening dispersion than those around it. No star appears above the Main Sequence at the faint end of the color-magnitude diagram. A distance modulus of V0−Mv=12.20±0.2 is obtained, which gives an age of about 5×106 yr. From only the photometry it is concluded to be slightly older than the nearby cluster Tr 16.